(untitled) (Journal of Human Sciences, 2024)
This research is based on the study of the views of Al Sadiq Al Nayhoum that are related to the miracles of the prophets, by extrapolating his authorship, presenting his statements, analyzing and criticizing them. It also highlights the importance of conducting the research, in intersection, to his understanding and views as a modernist figure influential on the cultural level. The research comes out in an introduction, an exploratory section, three proposed demands, and a conclusion. The main findings of this research have been focusing on the exegetical matters of Al Nayhoum’s attitudes towards the prophets’ miracles. Within the purview of the research, these convictions are found to deny them as his inductive-exegetic and the deductive-dogmatic interpretations (contrary to the religious texts) are mostly based on argumentative theses of Orientalists and that most of his claims adherent to the subject of the study lack the axiomatic foundations of scientific research.